2017
DOI: 10.4172/2167-1222.1000408
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Transcultural Aspect of Sexual Abuse of Children and Adolescents

Abstract: Sexual abuse toward children and adolescents is a global public health and human rights concern. Despite being a crime in most countries, and with well-known physical and mental health consequences, the majority of sexual offences are not reported. Child and adolescents sexual abuse is a maltreatment form characterized by contact or noncontact acts perpetrated by adults or older children toward younger children who have little power to resist. This overview aims to understand the social context of child sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…11,12 This is often because those affected tend to conceal their traumata because of shame and feelings of guilt, but also out of fear of being ostracised by their native community. 13,14 Among individuals who have experienced trauma with body contact, especially in the area of sexual violence, shame plays a particular role in the development of peritraumatic or post-traumatic symptoms, [15][16][17] and is linked to prolonged clinical problems. 18 Emphasising the central affective role of shame, 19 it has been suggested that PTSD, which often results from repetitive victimisation, especially sexual violence, can be conceptualised as both trauma disorder and shame disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 This is often because those affected tend to conceal their traumata because of shame and feelings of guilt, but also out of fear of being ostracised by their native community. 13,14 Among individuals who have experienced trauma with body contact, especially in the area of sexual violence, shame plays a particular role in the development of peritraumatic or post-traumatic symptoms, [15][16][17] and is linked to prolonged clinical problems. 18 Emphasising the central affective role of shame, 19 it has been suggested that PTSD, which often results from repetitive victimisation, especially sexual violence, can be conceptualised as both trauma disorder and shame disorder.…”
mentioning
confidence: 99%
“…11,12 This is often because those affected tend to conceal their traumata because of shame and feelings of guilt, but also out of fear of being ostracised by their native community. 13,14 Among individuals who have experienced trauma with body contact, especially in the area of sexual violence, shame plays a particular role in the development of peritraumatic or post-traumatic symptoms, 15–17 and is linked to prolonged clinical problems. 18…”
mentioning
confidence: 99%